2013
DOI: 10.3389/fnhum.2013.00367
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of auditory verbal hallucinations: lifetime prevalence, correlates and mechanisms in healthy and clinical individuals

Abstract: Over the years, the prevalence of auditory verbal hallucinations (AVHs) have been documented across the lifespan in varied contexts, and with a range of potential long-term outcomes. Initially the emphasis focused on whether AVHs conferred risk for psychosis. However, recent research has identified significant differences in the presentation and outcomes of AVH in patients compared to those in non-clinical populations. For this reason, it has been suggested that auditory hallucinations are an entity by themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
132
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 275 publications
(366 reference statements)
14
132
0
1
Order By: Relevance
“…4 AVH in children are usually transitory, resolving with time, unless they are associated with a severe underlying psychiatric illness. 5 AVH have also been reported in anxiety and posttraumatic experiences. 6 Depending on the traumatic experience, auditory hallucinations can change in character and quality.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…4 AVH in children are usually transitory, resolving with time, unless they are associated with a severe underlying psychiatric illness. 5 AVH have also been reported in anxiety and posttraumatic experiences. 6 Depending on the traumatic experience, auditory hallucinations can change in character and quality.…”
Section: Discussionmentioning
confidence: 94%
“…Other conditions that can present with predominantly visual hallucinations but can also include auditory hallucinations are migraines, dementia, narcolepsy, REM behavior disorder, and occipital seizures. 5 Treatment options for exclusively hypnagogic AVH are aimed at the underlying condition. Sleep extension is commonly recommended when sleep insufficiency is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…While cognitive models suggest that auditory hallucinations arise from the misattribution of inner speech to an external source, Allen et al, (2005) found that it was the influence of high levels of emotion, particularly anxiety, on cognitive functioning that was implicated in triggering hallucinations. Some support for this position was offered by de Leede-Smith and Barkus (2013) who, observing the close association between auditory hallucinations and PTSD, suggested that trauma acting on the individual via intrusive thoughts and memories may result in hallucinations. More specifically, Hugdahl (2009) proposed that hallucinations represented bottom-up perceptual misrepresentations due to a failure of top-down (cortical/pre-frontal) inhibition as a consequence of high levels of emotional stress.…”
Section: Pathways To Auditory Hallucinations and Some Associated Difmentioning
confidence: 99%
“…de Leede-Smith and Barkus (2013) were clear in their view that auditory hallucinations should no longer be recognized as a diagnostic indicator as the presence of such hallucinations is not intrinsically related to the outcome of the individual. Schreier (1998) considered that prognosis was likely to be more related to aspects of the child's condition rather than to the fact that they heard voices and, in a later paper (Schreier, 1999), advised that hallucinations seen in children needed to be regarded in the context of the rest of the clinical picture.…”
Section: Implications For Diagnosismentioning
confidence: 99%
See 1 more Smart Citation